Evaluation of customer service quality (SERVQUAL) of Prime Bank Limited - Reza, Tahsin Subah (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.